ENTERPRISE RISK MANAGEMENT AND ITS IMPACT ON CORPORATE PERFORMANCE: A STUDY ON MALAYSIAN PUBLIC LISTED COMPANIES - Lai, Fong Woon (2007)
In maximizing shareholder‟s wealth, management operational maneuver is typically calibrated to improve the valuation of the company‟s shares. But in the process, managers have to deal with a single most crucial element in corporate management: risk. This paper presents findings of a preliminary study of an ongoing research to examine the impact of the implementation of enterprise risk management (ERM) on corporate performance and value. ERM focuses risk management function from primarily defensive to increasingly offensive and strategic in nature. However, the neo-classical finance theory postulates that firm-specific risk is irrelevant and that only the covariance of the firm‟s asset returns to the market portfolio which is measured by the beta in the capital asset pricing model (CAPM) matters. This suggests that implementation of ERM is of no value to firms. To vindicate the theory, the authors test several hypotheses concerning the relationships between the ERM implementation process, the performance of the enterprise, as well as its effect on corporate risk profile. This study also examines the profile and the penetration depth of ERM practices among the listed companies. Results of the empirical analysis show that ERM practices do have an impact on business performance and corporate value. The results also imply that ERM implementation is consistent with the value maximization hypothesis.